The Suitability of Mangrove Ecotourism Based on Its Biophysical Condition in Hamadi Beach, Jayapura City - Annisa Novita Sari; Chandra Bhaskara; Aldi Bimantara (Journal of Indonesian Tourism and Development Studies, 2020)
Mangrove ecotourism is one of the potential sustainable tourism practices in which it is important to support local economic development and mangrove conservation. The purpose of this research is to identify the potential of natural resources in supporting mangrove ecotourism on the coast of Hamadi Beach, Jayapura City and to analyze the suitability of mangrove ecotourism land on the coast of Hamadi Beach, Jayapura City. The method used in this study is a survey method. The survey was conducted to see the biophysical condition of mangrove forests, which include mangrove length, mangrove density, mangroves species and biota species. Then, the biophysical data will be analyzed with Ecotourism Suitability Index (ESI). The survey results showed that the average mangrovesâ€™ length was 254 meters, the average mangrove density of 12,367 individuals.ha-1. Mangrove species found included Avicennia alba, Avicennia lanata, Avicennia marina, Acrostichum speciosum, Bruguiera sexangula, Rhizopora apiculata, Rhizopora mucronata, Rhizopora stylosa, and Sonneratia alba. The types of biota found consisted of birds, reptiles, amphibians, molluscs, crustaceans, and insects. The results of the suitability index of mangrove ecotourism obtained the Ecotourism Suitability Index (ESI) value of 77.78%. This study concludes that the mangrove forest area in Hamadi Beach is very suitable for ecotourism areas. Therefore, it is suggested to make a good and environmentally friendly ecotourism arrangement concept, so the community can travel while learning in the mangrove ecosystem area in Hamadi Beach.Keywords: Ecotourism, Hamadi Beach, mangrove forest.Â Â